Kajian Pengaruh Konsentrasi Asam Nitrat Terhadap Kemurnian Silika dari Batu Rijang - Nureztiti Azwar; Syamsi Aini (Departemen Kimia FMIPA UNP, 2020)
Chert is stone that contains silica (SiO2) ≥ 60%. High silica content in chert stones can be used as an alternative source of potential silica in synthesizing sodium silicate (Na2SiO3) or other industrial needs. Purification is used to separate silica from other metals contained in the chert stone using HNO3. The qualitative and quantitative analysis of chert stone with XRF reveal that it contained a small amount of impurity oxide such as Al2O3, Fe2O3, MgO, K2O, CaO with the highest contain is SiO2 about 79.99%. After several purification steps, silica percentage from the chert stone increased to 86.45%. With this increasing percentage of silica, its potential to use it as precursor Na2SiO3.